Anaesthetic management of a patient with non compaction cardiomyopathy for implantable cardioverter defibrillator lead replacement - Sharma, Kritika; Koli, Deepak; Daftary, Swati; Mehta, Hemant (International Journal of Research in Medical Sciences, 2020)
Non compaction cardiomyopathy (NCM) is a rare, primary genetically derived cardiomyopathy with a variable clinical presentation ranging from absence of symptoms to congestive heart failure, systemic thromboembolism, arrythmias and sudden cardiac death. Being an uncommon condition, the perioperative concerns in a patient with NCM have not been studied much. With increasing awareness and improved diagnostic tools including high resolution echocardiography and cardiac MRI, there has been an increase in the reporting of cases which stresses on the need for a complete understanding of this form of cardiomyopathy and its perioperative anaesthetic management. Authors report the case of a 24 years old female, with NCM who underwent prophylactic Implantable cardioverter defibrillator (ICD) insertion 5 years ago and was now posted for ICD removal and replacement in view of inappropriate ICD functioning.